CRISPR/Cas9-mediated VDR knockout plays an essential role in the growth of dermal papilla cells through enhanced relative genes - Ye Gao; Miaohan Jin; Yiyuan Niu; Hailong Yan; Guangxian Zhou; Yulin Chen (PeerJ, 2019)
Background Hair follicles in cashmere goats are divided into primary and secondary hair follicles (HFs). HF development, which determines the morphological structure, is regulated by a large number of vital genes; however, the key functional genes and their interaction networks are still unclear. Although the vitamin D receptor (VDR) is related to cashmere goat HF formation, its precise effects are largely unknown. In the present study, we verified the functions of key genes identified in previous studies using hair dermal papilla (DP) cells as an experimental model. Furthermore, we used CRISPR/Cas9 technology to modify the VDR in DP cells to dissect the molecular mechanism underlying HF formation in cashmere goats. Results The VDR expression levels in nine tissues of Shaanbei white cashmere goats differed significantly between embryonic day 60 (E60) and embryonic day 120 (E120). At E120, VDR expression was highest in the skin. At the newborn and E120 stages, the VDR protein was highly expressed in the root sheath and hair ball region of Shaanbei cashmere goats. We cloned the complete CDS of VDR in the Shaanbei white cashmere goat and constructed a VDR-deficient DP cell model by CRISPR/Cas9. Heterozygous and homozygous mutant DP cells were produced. The growth rate of mutant DP cells was significantly lower than that of wild-type DP cells (P < 0.05) and VDR mRNA levels in DP cells decreased significantly after VDR knockdown (P < 0.05). Further, the expression levels of VGF, Noggin, Lef1, and β-catenin were significantly downregulated (P < 0.05). Conclusions Our results indicated that VDR has a vital role in DP cells, and that its effects are mediated by Wnt and BMP4 signaling.